2010
DOI: 10.3767/003158510x486568
|View full text |Cite
|
Sign up to set email alerts
|

<I>Calonectria</I> species associated with cutting rot of <I>Eucalyptus</I>

Abstract: Decline in the productivity of Eucalyptus hybrid cutting production in the Guangdong Province of China is linked to cutting rot associated with several Calonectria spp. The aim of this study was to identify these fungi using morphological and DNA sequence comparisons. Two previously undescribed Calonectria spp., Ca. pseudoreteaudii sp. nov. and Ca. cerciana sp. nov. were identified together with Ca. pauciramosa. Calonectria pseudoreteaudii resides in the Ca. reteaudii complex and Ca. cerciana is closely relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
130
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(135 citation statements)
references
References 42 publications
3
130
1
1
Order By: Relevance
“…pteridis cause leaf spot on Phoenix canariensis and Serenoa repens, respectively (Luo et al 2009, Yang et al 2014. In forestry, leaf blight caused by Calonectria species is considered as one of the most serious threats to Eucalyptus plantations and nurseries in southern China (Zhou et al 2008, Lombard et al 2010a, Chen et al 2011. The leaf inoculations showed that all tested Calonectria species were pathogenic to the tested Eucalyptus clones, including the clones that are widely planted in southern China (Chen et al 2011, Li et al 2014a.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…pteridis cause leaf spot on Phoenix canariensis and Serenoa repens, respectively (Luo et al 2009, Yang et al 2014. In forestry, leaf blight caused by Calonectria species is considered as one of the most serious threats to Eucalyptus plantations and nurseries in southern China (Zhou et al 2008, Lombard et al 2010a, Chen et al 2011. The leaf inoculations showed that all tested Calonectria species were pathogenic to the tested Eucalyptus clones, including the clones that are widely planted in southern China (Chen et al 2011, Li et al 2014a.…”
Section: Discussionmentioning
confidence: 99%
“…To date 27 Calonectria species have been isolated from Eucalyptus tissues with CLB/leaf rot symptoms or from soils originating from Eucalyptus plantations in tropical or subtropical areas in FuJian, GuangDong, GuangXi and HaiNan Provinces (Crous et al 2004, Lombard et al 2010a, Chen et al 2011. However, little information is known about the species diversity of Calonectria in natural forests.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaf blight and other foliar diseases induced by C. eucalypti can easily be confused with those caused by other plant-pathogenic fungi, such as Mycosphaerella spp. and their anamorphs (Cheewangkoon et al 2008(Cheewangkoon et al , 2009Crous 2009), and Calonectria (Crous et al 2004b(Crous et al , 2006aLombard et al 2009Lombard et al , 2010.…”
Section: Introductionmentioning
confidence: 99%